ANALISIS KUALITAS WEBSITE TERHADAP KEPUASAN PENGGUNA MENGGUNAKAN METODE WEBQUAL 4.0 (STUDI KASUS : WEBSITE SEKOLAH KITA) - Nurhayati Nurhayati; Manja Purnasari; Zulfi Karman; Yessi Hartiwi (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to analyze the quality of the sekolah.data.kemdikbud.go.id website and its effect on user satisfaction using the Webqual 4.0 method. The method evaluates three main dimensions: usability quality, information quality, and interaction quality, which are then assessed for their influence on user satisfaction through SmartPLS analysis. Data were collected via an online questionnaire completed by 200 respondents. The results indicate that all three Webqual dimensions have a positive and significant effect on user satisfaction. Among them, interaction quality shows the strongest influence with original sample value 0.531. This research highlights the importance of improving interaction quality and information delivery to enhance user experience on educational service websites.